Partial ambulatory management of severe secondary spontaneous pneumothorax. (2017) - Masih, Izhaq; Vali, Yusuf; Naeem, Muhammed; Reddy, R.V.
Abstract: Secondary spontaneous pneumothorax can be difficult to manage especially in patients with advanced lung disease and respiratory failure. Such patients are unfit for surgery and may endure prolonged hospital stays with chest drains in situ. We describe two such cases where the air leak was persistent despite conventional management. Ambulatory devices which we ordinarily use to manage pneumothoraces in patients with a good lung reserve, were employed as a palliative measure. The strategy not only allowed the patients to return home, but also resulted in healing of the air leak which had persisted with conventional management.